2000
DOI: 10.1161/01.res.87.7.623
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Aorta and Vena Cava Medial Message Expression by cDNA Array Analysis Identifies a Set of 68 Consistently Differentially Expressed Genes, All in Aortic Media

Abstract: Abstract-We performed a systematic analysis of gene expression in arteries and veins by comparing message profiles of macaque aorta and vena cava media using a cDNA array containing 4048 known human genes, Ϸ35% of currently named human genes (Ϸ11 000). The data show extensive differences in RNA expression in artery versus vein media. Sixty-eight genes had consistent elevation in message expression by the aorta, but none were elevated in the vena cava. The most differentially expressed gene was regulator of G-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 40 publications
5
93
0
1
Order By: Relevance
“…35 RGS5 has also been identified by microarray analysis of genes expressed in the media of human aorta but not vena cava, suggesting specific arterial expression. 24 In a search for genes differentially expressed in a genetic rat model for stroke, Kirsch and colleagues 25 found RGS5 to be down-regulated, and they localized RGS5 expression in the rat CNS to capillary endothelium and the plexus choroideus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 RGS5 has also been identified by microarray analysis of genes expressed in the media of human aorta but not vena cava, suggesting specific arterial expression. 24 In a search for genes differentially expressed in a genetic rat model for stroke, Kirsch and colleagues 25 found RGS5 to be down-regulated, and they localized RGS5 expression in the rat CNS to capillary endothelium and the plexus choroideus.…”
Section: Discussionmentioning
confidence: 99%
“…The most down-regulated gene, encoding a member of the RGS family of regulators of G protein signaling, RGS5, caught our attention, because this gene has previously been reported to have a vascular expression pattern. 24,25 …”
Section: Cdna Microarray Hybridizations Identify Rgs5 As a Down-regulmentioning
confidence: 99%
“…(2) At a physiologic and molecular levels, veins tend to produce less NO and prostacyclin, which could predispose to endothelial injury (25). Recent studies have also demonstrated significant differences in gene expression between normal arteries and veins (26). Whether differences in the expression of these genes translates into a more aggressive response to injury is unknown.…”
Section: Pathogenesis Of Avf and Ptfe Graft Failurementioning
confidence: 99%
“…Additionally, changes in the local environment of the cells or cell-matrix interactions can affect the phenotypic state of VSMC (19,20). With the advent of microarray technology, it is feasible to (21), between the aorta and vena cava (22), in mechanically stimulated SMC (23), and between neointimal and aortic SMC (24). However, a comprehensive analysis of changes in gene expression induced by hypertrophic stimuli compared with PDGF has yet to be investigated.…”
mentioning
confidence: 99%